Анализ влияния магнитной проницаемости стальных элементов железобетонных конструкций домов на уровень ослабления геомагнитного поля в помещениях - Грецких, Светлана Владимировна (НТУ "ХПИ", 2015)
Показано, что использование в строительстве стандартного арматурного проката приводит к опасному ослаблению геомагнитного поля в помещениях. Определены требования к магнитной проницаемости "слабомагнитной" конструкционной стали (μн<70), применение которой в жилищном строительстве позволит обеспечить комфортные условия проживания по магнитному полю.

It is shown that the use in the construction of standard reinforcing bars leads to a dangerous weakening of the geomagnetic field on the premises. The requirements for the magnetic permeability "weakly magnetic" structural steel (μн < 70) are established. The use of these requirements in residential construction will provide comfortable accommodation in the magnetic field.
Analysis of the influence of the magnetic permeability of the steel reinforced concrete structures on the level of the geomagnetic field inside premises
Keywords: магнитная проницаемость; конструкционная сталь; геомагнитное поле; железобетонные строительные конструкции; арматура; magnetic permeability; structural steel; geomagnetic field; reinforced concrete constructions